KONSEP ADIL DALAM POLIGAMI MENURUT IMAM SYAFI’I - Jajuli Jajuli; Damanhuri Damanhuri (STAI Darussalam Lampung, 2024)
Polygamy constitutes a legal institution in Islam whose permissibility is normatively accompanied by the requirement of justice. However, the concept of justice in polygamy has not been uniformly understood by Muslim scholars, resulting in divergent interpretations within the practice of Islamic family law. This article aims to analyze the concept of justice as a condition for polygamy according to Imam al-Shafi‘i by examining its normative foundations in the Qur’an, the Sunnah, and the views of Shafi‘i jurists. This study employs library research using a normative–doctrinal approach. The data are derived from primary sources, including the Qur’an, hadith, and classical fiqh texts of the Shafi‘i school, as well as secondary sources in the form of relevant scholarly literature. The findings indicate that, according to Imam al-Shafi‘i, justice in polygamy is positioned as a religious obligation rather than a condition for the legal validity of marriage. The required justice is limited to outward and measurable aspects, such as financial maintenance, residence, and the equitable distribution of time, whereas inner justice related to emotional inclination is not stipulated as a condition, as it lies beyond human capacity. This concept reflects Imam al-Shafi‘i’s moderate approach in balancing the normative demands of Islamic law with human realities and demonstrates its relevance for the development of contemporary Islamic family law.